MORPHOLOGICAL CHANGES IN LIVER TISSUE OF RABBITS WITH EXPERIMENTAL METABOLIC SYNDROME UNDER THE INFLUENCE OF A MODIFIED KETOGENIC DIET (Global Conference on Medical and Health Sciences, 2026)
Metabolic syndrome is one of the leading medical and social problems worldwide and is associated with profound metabolic disturbances, including insulin resistance, dyslipidemia, chronic inflammation, and hepatic dysfunction. The liver is one of the primary target organs affected by metabolic syndrome, where excessive lipid accumulation leads to structural alterations, hepatocyte injury, and progressive impairment of hepatic function. Histological evaluation of liver tissue provides valuable information regarding the severity of hepatic damage and the effectiveness of therapeutic interventions. Modified ketogenic diets have recently emerged as promising non-pharmacological approaches for correcting metabolic disorders; however, their effects on liver morphology remain insufficiently investigated.
Keywords: insulin resistance, dyslipidemia, chronic inflammation, and hepatic dysfunction